Perancangan Sistem Drone Pertanian Berbasis Tata Kelola TI dengan Pendekatan TOGAF - Anugrahaningtyas Pramurwitasari; Maulida Khoiru Nisa; Sigmawan Malikul Rahman; Taqy Muhammad Fadhil; M. Narjun Najich (Universitas Aisyiyah Surakarta, 2026)
Agricultural modernization in Indonesia faces challenges such as labor constraints, fertilizer efficiency, and low adoption of information systems. Agricultural drone technology offers innovative solutions, but structured implementation based on IT governance remains limited. This study used a descriptive qualitative approach to design a drone system based on the TOGAF ADM enterprise architecture. Data were collected through observations, semi-structured interviews, technical documentation, and a survey of 25 farmers in Andong District, Boyolali Regency. The system was designed by mapping the business architecture, application, data, and technology domains, and validated through surveys and expert discussion forums. The results showed that the modular and integrated drone system aligned with business objectives; the survey revealed that 80% of farmers experienced difficulties with manual fertilization, 88% were interested in using drones, and the average digital readiness score was 3.24/5. The drone is equipped with GPS, NDVI sensors, fertilizer tanks, a dashboard, and a mobile app for control and monitoring. The TOGAF approach has been proven to provide a comprehensive structure, supporting technology integration, IT governance, and sustainable implementation, making this system effective in improving efficiency, fertilization accuracy, and readiness for digital technology adoption.